2022
DOI: 10.1038/s41598-022-13724-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell type specific cannabinoid CB1 receptor distribution across the human and non-human primate cortex

Abstract: Alterations in cannabinoid CB1 receptor (CB1R) are implicated in various psychiatric disorders. CB1R participates in both depolarization induced suppression of inhibition (DSI) and depolarization induced suppression of excitation (DSE), suggesting its involvement in regulating excitatory and inhibitory (E/I) balance. Prior studies examining neuronal cell type specific CB1R distribution have been conducted near exclusively within rodents. Identification of these distribution patterns within the human and non-hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…1a, b & d). The wide distribution and staining pattern of CB1R in the cortical layers evaluated was aligned with the existing literature for other brain regions 43 . Speci cally, our analysis revealed a positive colocalization with CB1R, con rming its expression by astrocytes in the cortical layers examined of the mPFC (Fig.…”
Section: Mpfc Astrocytes Respond To Endocannabinoidssupporting
confidence: 79%
“…1a, b & d). The wide distribution and staining pattern of CB1R in the cortical layers evaluated was aligned with the existing literature for other brain regions 43 . Speci cally, our analysis revealed a positive colocalization with CB1R, con rming its expression by astrocytes in the cortical layers examined of the mPFC (Fig.…”
Section: Mpfc Astrocytes Respond To Endocannabinoidssupporting
confidence: 79%
“…Cannabis is one of the most commonly used psychotropic substances in the United States (Azofeifa et al, 2016; Carliner et al, 2017) and its main psychoactive component is ∆ 9 -tetrahydrocannabinol (Bloomfield et al, 2019; Chou et al, 2022), which serves as an agonist of the endocannabinoid CB 1 and CB 2 receptors (Howlett and Abood, 2017). Cannabis has been shown to reduce inflammation in PWH (Ellis et al, 2020, 2021; Manuzak et al, 2018) by acting on CB 2 receptors found primarily on immune cells that modulate the release of inflammatory cytokines (Hall and Degenhardt, 2009; Skosnik et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated successful and specific vGAT and vGlut1 labeling in human and non-human primate postmortem studies using these antibodies (48)(49)(50)(51). The CB1R antibody demonstrated successful co-labeling with both vGAT and vGlut1 in both neuronal cultures and postmortem human brain samples (21,52). In addition, vGAT and CB1R antibody specificities were validated through knockout samples (53,54), and vGlut1 antibody through pre-adsorption controls (Millipore certificate of analysis, 2016).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…A ubiquitous G-protein coupled receptor (GPCR) (17), CB1R is highly expressed within the cholecystokinin (CCK) subtype GABAergic inhibitory interneurons within the human cortex (18,19). However, it is also found in other interneuronal subtypes and glutamatergic neurons (20,21). Functionally, presynaptic CB1R activation results in reduced synaptic transmission by attenuating neurotransmitter release, a phenomenon known as depolarization-induced suppression of inhibition (DSI) at inhibitory boutons, and depolarization-induced suppression of excitation (DSE) at excitatory sites (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation